1982
DOI: 10.1073/pnas.79.7.2245
|View full text |Cite
|
Sign up to set email alerts
|

Use of monoclonal antibodies to subunits of human chorionic gonadotropin to examine the orientation of the hormone in its complex with receptor.

Abstract: Monoclonal antibodies were prepared against the a and f8 subunits of human chorionic gonadotropin (hCG). Although all were selected on the basis of their ability to bind the intact hormone, each also bound one of the two subunits but not both. Using a solid phase double antibody system to measure the relative binding to sites on the surface of hCG, we observed that four ofthe five antibodies bound to different sites on the molecule. This information was correlated with the ability of each antibody to inhibit t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(36 citation statements)
references
References 21 publications
2
34
0
Order By: Relevance
“…Hormone and analog heterodimers released into the medium were quantified using a sandwich immunoassay similar to one we reported (29) except that different antibodies and standards were used, depending on the hormone or analog being measured. To quantify heterodimers consisting of human/bovine ␣-subunit chimeras and hCG ␤-subunits, we captured the analogs with an anti-␤-subunit antibody (B112) having high affinity for an hCG ␤-subunit epitope that included Asn 77 (28).…”
Section: Methodsmentioning
confidence: 99%
“…Hormone and analog heterodimers released into the medium were quantified using a sandwich immunoassay similar to one we reported (29) except that different antibodies and standards were used, depending on the hormone or analog being measured. To quantify heterodimers consisting of human/bovine ␣-subunit chimeras and hCG ␤-subunits, we captured the analogs with an anti-␤-subunit antibody (B112) having high affinity for an hCG ␤-subunit epitope that included Asn 77 (28).…”
Section: Methodsmentioning
confidence: 99%
“…It was precisely shown that which amino-acids of the alpha-subunit are implicated in the interaction with gonadotropin receptors. Some earlier studies based on photo affinity labelling (Hong et al 1999;Sohn et al 2002) immunological studies (Moyle et al 1982) and mutational studies (Yoo et al 1991;Zeng et al 1995;Arnold et al 1998) demonstrated that the alpha subunit also interacts with the receptor. However, we report for the first time, the predicted three dimensional structures of the mature alpha subunit of eCG and its molecular docking with ganirelix which may play role in elaborating the responsibility played by alpha subunit of eCG in the process of reproduction and maintenance of pregnancy in equines as well as other species.…”
Section: Discussionmentioning
confidence: 99%
“…They were transfected into COS-7 cells obtained from ATCC (Manassas, VA) using a calcium phosphate procedure (13). Secreted analogs were harvested 3 days after transfection and analyzed in monoclonal antibody sandwich immunoassays (14) employing antibodies A113 and B401, obtained from Dr. William Munroe (Hybritech Inc., a division of Beckman Coulter, Inc., San Diego, CA) and B110 produced as described (15). Antibody A113 recognizes conformation-dependent ␣-subunit epitopes in the heterodimer.…”
Section: Methodsmentioning
confidence: 99%